2013
DOI: 10.1002/acr.22049
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Foot Posture and Function to Lower Extremity Pain: Results From a Population‐Based Foot Study

Abstract: Objective Studies have implicated foot posture and foot function as risk factors for lower extremity pain. Empirical population-based evidence for this assertion is lacking; therefore, the purpose of this study was to evaluate cross-sectional associations of foot posture and foot function to lower extremity joint pain in a population-based study of adults. Methods Participants were members of the Framingham Foot Study. lower extremity joint pain was determined by the response to the NHANES-type question, “On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 60 publications
1
61
0
1
Order By: Relevance
“…Whereas foot type is related to foot function [2,13], it is important to perceive the difference of foot arch between ages and genders, to help prevent risk of injuries [14].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas foot type is related to foot function [2,13], it is important to perceive the difference of foot arch between ages and genders, to help prevent risk of injuries [14].…”
Section: Discussionmentioning
confidence: 99%
“…[9] Several recipient sites are available for temporary ectopic implantation, including the groin, lower leg, foot, and opposite arm and hand. [4][5][6][7] Selection is generally based on matching the vessels between the recipient site and the implanted part. In our case, a venous network on the dorsum of the foot was presented, which can be included in the dorsalis pedis fasciocutaneous flap.…”
Section: Discussionmentioning
confidence: 99%
“…The disability score for the arm, shoulder, and hand [6] was 78. Based on a foot function assessment, [7] the patient reported no foot pain and had no difficulty when he stood on tiptoe or walked in the house. The patient had no difficulty when he walked outside for four blocks, climbed or descended stairs, got up from a chair, climbed curbs, ran, or walked quickly.…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…14 The incidence of hallux valgus is 3%, 9%, and 16% for age 15 to 30, 31 to 60 and above 60 respectively. 13 The natural prognosis of all adductus anomalies, except CTEV has been shown to be positive. Prospective monitoring showed that for 87% and 95% of children at age of 6 and 16 years respectively, the adductus anomalies had resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Pes-planus on the other hand is characterized by a low longitudinal arch, and is normal in young children and resolves as the child grows. 11,12 Hallux Valgus is commonly associated with pesplanus, and is also considered as a genetic anamoly, 13 the incidence of which is amplified with age. Pes planus is also found to influence tibiofemoral angle resulting in valgus angulation at the knee.…”
Section: Introductionmentioning
confidence: 99%